(untitled) (Journal of the Management Sciences, 2025)
This paper examines whether a structural shift has occurred in customer preference from Automated Teller Machine (ATM) transactions to Point of Sale (POS) transactions in Nigeria’s payment system between 2012 and 2023. Using transaction volume and transaction value, the study captures both behavioral usage patterns and monetary dynamics. Results show that POS transaction volumes grew sharply from 1.4 million in 2012 to 130 million in 2023, averaging 78.5% annual growth, while ATM transactions rose from 234 million to 420 million, at a modest 7.7% annual growth. In value terms, POS expanded from ₦51 billion to ₦5,430 billion, outpacing ATM growth from ₦1,530 billion to ₦4,330 billion. These trajectories highlight POS as the faster-growing channel, both in scale and financial relevance. Regression analysis reveals a strong association between ATM and POS growth, with ATM growth explaining 82.1% of POS growth in volumes (β = 9.94, p < 0.001) and 79.4% in values (β = 1.82, p < 0.001). Paired t-tests confirm that POS growth rates significantly exceeded ATM growth rates (t = 5.60, p < 0.001; t = 4.641, p < 0.001). The null hypothesis of no significant shift is decisively rejected. Evidence points to a clear transition in customer preference toward POS, reflecting Nigeria’s accelerating adoption of digital retail payment systems and reinforcing the trajectory of its cashless policy agenda. It is recommended that policymakers expand digital infrastructure, improve transaction security, and enhance financial literacy to sustain this momentum and deepen trust in POS-driven payment channels.